Atrial fibrillation in the patients with obesity and arterial hypertension - N. S. Tsyplenkova; E. I. Panova; N. V. Zhdankina; E. P. Morozova; O. V. Karataeva (SINAPS LLC, 2015)
We have examined 184 working-aged police officer men who have been suffering from arterial hypertension (AH). It was found that obesity in this group of patients significantly increases frequency of atrial fibrillation. Moreover, it was established that there is a direct relationship between arrhythmia and degree of obesity. The main risk factors of atrial fibrillation in men with obesity are AH II-III stage, left ventricular and left atrium dilatation, low level of high density lipoproteins in serum, abnormal daily profile of blood pressure (non-dipper type). We have not revealed the presence of the association between atrial fibrillation, age and ischemic heart disease in obese patients.